Amphibians from Serra do Cipó, Minas Gerais, Brasil. VI: A New Species of the Physalemus deimaticus Group (Anura, Leptodactylidae) - Leal, Fernando; Leite, Felipe S. F.; Costa, William P. Da; Nascimento, Luciana B.; Lourenço, Luciana B.; Garcia, Paulo C. A. (Zootaxa, 2020)
We describe a new species of Physalaemus assigned to the Physalaemus signifer Clade, and it is morphologically similar to P. rupestris, from the highlands of the Serra do Cipó in the southern Espinhaço Range, State of Minas Gerais, Southeastern Brazil. The new species is diagnosed by using the following combination of character states: presence of an arrow-shaped blotch on the dorsum of body; presence of a median longitudinal light stripe over urostyle region; belly and ventral surface of thigh marbled with dark gray irregularly shaped blotches on a bluish background; absence of reddish coloration over axillary and inguinal regions in live individuals; bright orange dots scattered over head, upper lip, and dorsum of body in live individuals; ventral surface of hand and foot red in live individuals; small size (adult male SVL=16.2–18.2 mm); presence of brown, not divided, nuptial pad in males; END/ED in males ranging from 0.85–0.93; supernumerary tubercles on foot absent; tarsal fold absent; tarsal tubercle absent; texture of posterior region of belly and ventral surface of thigh smooth; advertisement call composed of two note types (note A + B); advertisement call duration of 0.80–1.28 s; note A with ascending amplitude until mid-note then descending towards the end of the note; note B with pulses arranged in 5–7 groups; and dominant frequency of note A from 1734.4–2765.6 Hz and of note B from 1507.3–2859.4 Hz. A phylogenetic analysis based on mitochondrial DNA sequences recovered the new species nested within the Physalaemus deimaticus species group. Additionally, we redescribe the call of Physalaemus rupestris and provide a review of the geographic distribution and conservation status of the species belonging to the P. deimaticus species group.